Scale-aware space-time stochastic parameterization of subgrid-scale velocity enhancement of sea surface fluxes - Bessac, Julie; Christensen, Hannah M.; Endo, Kota; Monahan, Adam H.; Weitzel, Nils (Journal of advances in modeling earth systems, 2021)
Stochastic representation of the influence of the subgrid-scales on the resolved scales in weather and climate models has been shown to improve ensemble spread and resolved variability. We propose a statistical scale-aware space-time model to characterize the contribution of mesoscale wind variability to air-sea exchanges. In an earlier study, we analyzed the difference between “true” fluxes computed from a high resolution simulation and “resolved” fluxes obtained by coarse graining. This discrepancy is modeled in space and time, conditioned on the coarse-grained wind and precipitation fields, to parameterize the enhancement of fluxes by mesoscale velocity variations. Stochastic parameterization models have traditionally been developed for particular model resolutions without the explicit capability to adapt to model resolution. We present an approach to develop stochastic models that adapt to resolution in a scale-aware fashion. The scale-aware parameterization is developed from empirical results for systematically coarse-grained high-resolution numerical model output. The statistical model is fit from numerical model output at three different coarsening resolutions. From this scale-aware parameterization, we derive a stochastic parameterization of flux enhancement by subgrid velocity variations for arbitrary resolutions and characterize the conditional distributions and space-time structures of the flux enhancement across model resolutions.
Gesehen am 28.06.2021